EFFECT OF TAX PLANNING, CAPITAL INTENSITY AND LEVERAGE ON COMPANY FINANCIAL PERFORMANCE (EMPIRICAL STUDY OF MANUFACTURING COMPANIES IN THE BASIC MATERIALS SECTOR LISTED ON THE INDONESIAN STOCK EXCHANGE 2017-2021). - Irfan Dwi Nurcahya; Ismawati, Iis; Soleha, Nurhayati (Review of Accounting and Taxation, 2024)
Abstract Purpose - The aim of this research is to see how tax planning, capital intensity, and leverage affect business financial performance using data from basic materials industrial manufacturing companies listed on the Indonesia Stock Exchange from 2017 to 2021. Design/methodology/approach - This research uses a quantitative multiple linear regression model. Purposive sampling was used and resulted in 47 companies with a total of 162 observation data. Data analysis was carried out using SPSS 25. Finding – Based on research findings, leverage has a negative impact on the company's financial performance, although capital intensity and tax planning both significantly improve financial performance. Originality – Paper Type – Research Paper